INDURSKY, Freda e FERREIRA, Maria Cristina Leandro (Orgs.). Os múltiplos territórios da Análise do Discurso. Porto Alegre, Sagra Luzzatto, 1999, 325p. - Payer, Onice (Organon, 2002)
INDURSKY, Freda e FERREIRA, Maria Cristina Leandro(Orgs.). Os múltiplos territórios da Análise do Discurso.Porto Alegre, Sagra Luzzatto, 1999, 325p.Resenhado por: M. Onice Payer